Total quality management in higher education in Malaysia : A case study. - Kassim, Zakaria (1996)
Almost everyone agrees that quality' is a performance standard . to be practised at all· times for the purpose of a "continuous effort to improve; but,not everyone agrees on the critenan, standards and indicators . (including performance and knowledge indicators)used to measure'the quality of services, especially related to the standard of human perfomance.